Household Wellbeing of Program Perumahan Rakyat in Johor Bahru: A Preliminary Analysis - Nur Faradiyana, Tahir; Wilson Rangga, Anthony Jiram; Salfarina, Samsudin; Aminah, Mohsin (2020)
In the present climate, most low and middle-income households are affected by market conditions; hence the positive impact of household wellbeing is difficult to achieve as expected. This paper examines the social and economic wellbeing of Program Perumahan Rakyat (PPR) scheme in Johor Bahru by collecting 109 survey data to provide a full picture of the extended coverage of household wellbeing dimension. A cross-sectional survey was employed to establish research objectives, and the survey data were analysed by using the Relative Importance Index analysis. The results indicated that the number of households, number of bedroom and bathroom, monthly consumption, monthly income, and housing quality are the factors that extremely influencing household wellbeing of the PPR scheme.